Q: 4 - 3x 6 - 4x?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

- 3X - (- 4X) is the same as - 3X + 4X X(- 3 + 4) that is all the factoring needed there

If: 3x+5 = 4x+1 Then: x = 4

10

4x + -x = 3x

5x + 6 - 2x = -5 - x Reduce the x variables on the left side of the equation: 3x + 6 = -5 -x Move the x variables to the same side of the equation 3x + x + 6 = -5 - x + x 4x + 6 = -5 Move the non-variable numbers to the other side of the equation 4x + 6 - 6 = -5 - 6 4x = -11 Divide by 4, to give you x on its own 4x/4 = -11/4 x = -11/4 = -2.75

Related questions

(6-4x)(x-2)+3x =6x-12-4x+8x+3x =5x-4

If you mean: 3x-(2x+4x-6) then 3x-2x-4x+6 simplifies to 6-3x

4x-10

4x-y=2, thereforey=4x-2sub y into 3x+2y=6...3x+8x-4=611x=10x=10/11

4x+3y = 6 3y = -4x+6 y = -4/3x+2 in slope intercept form

7-3x = -4x + 13x = 6

- 3X - (- 4X) is the same as - 3X + 4X X(- 3 + 4) that is all the factoring needed there

-4x + 5 + 3x + 6 = -x + 11

3x + 4 = 4x - 5 Add 5 to both sides: 3x + 9 = 4x Subtract 3x from both sides: 9 = x

So -3x - 6 = x - 4, ie -2 = 4x so x = -½ and y = -4½

Do you mean: 4x-8/3x-6 = 4/3 If so then the value of x works out as 0

3x2 + 4x factors to x(3x + 4)